80‐2: Invited Paper: Ink Jet Printed Film Formation and Its Impact on OLED Device Performance. Issue 1 (29th May 2019) - Bernatz, Georg; Béalle, Gaëlle; Hamburger, Manuel; Tseng, Hsin-Rong; Stolz, Sebastian; Hayer, Anna; Koenen, Nils; Linge, Rouven; Engel, Miriam; Meyer, Sebastian; Anemian, Rémi; Boehm, Edgar
Abstract : Flat and homogeneous films by ink jet printing of organic materials are proven to be essential for OLED application. The impact of ink formulation, film thickness, pixel size, bank layout and process conditions (i.e. drying parameters) have been investigated. Their severe impact on device performance is illustrated.